High miscarriage rate in women treated with Essure® for hydrosalpinx before embryo transfer: a systematic review and meta-analysis - Barbosa, M.W.; Sotiriadis, Alexandros; Papatheodorou, Stefania; Mijatovic, Velja; Nastri, Carolina Oliveira; Martins, Wellington (My University, 2016)
Objectives: Essure® has been tested as an alternative treatment for hydrosalpinx before embryo transfer (ET) in women undergoing assisted reproduction techniques. However, the persistence of a foreign body inside the uterine cavity might have a negative impact on the outcome of pregnancy. The present systematic review aimed at identifying, appraising and summarizing the available evidence regarding the effectiveness and safety of using Essure prior to ET for women with hydrosalpinx. Methods: We searched for studies in PubMed, Scopus, CENTRAL, Web of Science and ClinicalTrials.gov and the reference lists of eligible studies. All studies including at least 10 women with hydrosalpinx who received Essure, any other intervention or no treatment prior to ET were considered eligible. Study selection, data extraction and evaluation of the risk of bias were performed independently by two authors. Study outcomes were miscarriage per clinical pregnancy, singleton preterm birth per singleton live birth and live birth/ongoing pregnancy and clinical pregnancy per ET. The pooled results for each outcome and intervention were summarized as proportions with their respective 95% CIs, using a random-effects model. Results: Our electronic search of databases was performed on 7 November 2015, and 26 studies with 43 study arms were considered eligible: eight study arms evaluating Essure; seven assessing tubal aspiration; seven appraising effects of no treatment; 12 evaluating salpingectomy; two assessing tubal division; and seven evaluating tubal occlusion. When compared with women who had no intervention, women with Essure had a higher clinical pregnancy rate per ET (36% (95% CI, 0–43%) vs 13% (95% CI, 9–17%)). When compared with women who had other interventions, women with Essure had a higher miscarriage rate per clinical pregnancy (38% (95% CI, 27–49%) vs 15% (95% CI, 10–19%)). Conclusions: The available evidence suggests that, although Essure prior to ET in women with hydrosalpinx improves the chance of achieving a clinical pregnancy compared with no intervention, it is associated with a higher rate of miscarriage when compared with the other interventions. Although this evidence is based on observational studies, we believe that salpingectomy should be the first option for women who are eligible for videolaparoscopy. However, it is still premature to make recommendations for women who are not eligible for surgery, and randomized controlled trials are needed to clarify which is the best treatment alternative in such a scenario. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Infertility; IVF; Embryo transfer; Assisted reproductive technique; Essure; Hydrosalpinx